ANALISIS FAKTOR â FAKTOR YANG MENDORONG TINDAKAN TAX EVASION PADA WAJIB PAJAK UMKM DI KECAMATAN MADIDIR KOTA BITUNG - Palowa, Arif A.; Nangoi, Grace B.; Gerungai, Natalia Y. T. (JURNAL RISET AKUNTANSI GOING CONCERN, 2018)
The needs of local governments to the central government in the framework of financing and the level of community compliance to pay taxes in accordance with what is owed is the focus that needs to be discussed. For this reason, this study aims to analyze the factors that encourage tax evasion according to individual taxpayers in Madidir District, Bitung City. This type of research is qualitative descriptive, and the data used is primary data. Data obtained through direct interviews with seven informants in the city of Bitung based on the results of research on the analysis of factors - factors that encourage tax evasion in the form of reducing, removing, and illegal manipulation of tax burden according to taxpayers in Madidir Subdistrict, Bitung City can be concluded that the driving factor society takes action tax evasion is a fare factor that makes the tax burden to be high, economic factors, taxes system factor that too complicated, compliance factors that aim to enrich themselves, the government firmness factor, and distrust of the government bureaucracy.Keywords: tax, factors, tax evasion.